Directions of Poland’s foreign and security policy in the Euro-Atlantic region after 2018 (Economic and Political Thought, 2019)
The objective of this paper is to propose such directions of Poland’s foreignpolicy and security policy in the Euro-Atlantic zone after 2018 whichwould maximise opportunities and minimise threats identified in the assessmentof the country’s internal considerations on the one hand, and status ofPoland’s bilateral relations with individual countries, Poland’s multilateralrelations with NATO and the European Union and developments in the internationalpolitics worldwide in 1999–2018 on the other. Given the predefinedlimitations as to the length of this study, the objective has been achievedthrough: (i) a discussion of Poland’s selected objective internal considerations(geography; demographic, economic and military potentials); (ii) an analysisof Poland’s relations with Germany, France, the US, Belarus, Ukraine andRussia, as well as Poland’s contractual interrelations with NATO and theEuropean Union; (iii) attempt at classifying these considerations and factorsinto opportunities and threats; (iv) description of such proposed directionsof Poland’s foreign policy and security policy in the Euro-Atlantic zone after2018 which would maximise opportunities/minimise threats thus identified.The analysis assumes the following research hypothesis: changes in the internationalenvironment, as well as in Poland’s bilateral and multilateral internationalrelations render it necessary to revise and adjust directions of Poland’sforeign policy and security policy so that Poland’s position both within Europeand globally would be rebuilt, and that Poland’s security would be enhanced.
Keywords: Poland’s foreign policy, Poland’s security policy, Euro-Atlantic zone, NATO, European Union